Transcending the challenge of evolving resistance mechanisms in Pseudomonas aeruginosa through β-lactam-enhancer-mechanism-based cefepime/zidebactam - Andrea M. Hujer; Steven H. Marshall; Andrew R. Mack; Kristine M. Hujer; Yamuna Devi Bakthavatchalam; Kushal Umarkar; Snehal R. Palwe; Swapna Takalkar; Prashant R. Joshi; Rahul Shrivastava; Hariharan Periasamy; Sachin S. Bhagwat; et al. (mBio, 2023)
ABSTRACTMulti-drug resistant (MDR) Pseudomonas aeruginosa harbor a complex array of β-lactamases and non-enzymatic resistance mechanisms. In this study, the activity of a β-lactam/β-lactam-enhancer, cefepime/zidebactam, and novel β-lactam/β-lactamase inhibitor combinations was determined against an MDR phenotype-enriched, challenge panel of P. aeruginosa (n = 108). Isolates were multi-clonal as they belonged to at least 29 distinct sequence types (STs) and harbored metallo-β-lactamases, serine β-lactamases, penicillin binding protein (PBP) mutations, and other non-enzymatic resistance mechanisms. Ceftazidime/avibactam, ceftolozane/tazobactam, imipenem/relebactam, and cefepime/taniborbactam demonstrated MIC90s of >128 mg/L, while cefepime/zidebactam MIC90 was 16 mg/L. In a neutropenic-murine lung infection model, a cefepime/zidebactam human epithelial-lining fluid-simulated regimen achieved or exceeded a translational end point of 1−log10 kill for the isolates with elevated cefepime/zidebactam MICs (16–32 mg/L), harboring VIM-2 or KPC-2 and alterations in PBP2 and PBP3. In the same model, to assess the impact of zidebactam on the pharmacodynamic (PD) requirement of cefepime, dose-fractionation studies were undertaken employing cefepime-susceptible P. aeruginosa isolates. Administered alone, cefepime required 47%–68% fT >MIC for stasis to ~1 log10 kill effect, while cefepime in the presence of zidebactam required just 8%–16% for >2 log10 kill effect, thus, providing the pharmacokinetic/PD basis for in vivo efficacy of cefepime/zidebactam against isolates with MICs up to 32 mg/L. Unlike β-lactam/β-lactamase inhibitors, β-lactam enhancer mechanism-based cefepime/zidebactam shows a potential to transcend the challenge of ever-evolving resistance mechanisms by targeting multiple PBPs and overcoming diverse β-lactamases including carbapenemases in P. aeruginosa.IMPORTANCECompared to other genera of Gram-negative pathogens, Pseudomonas is adept in acquiring complex non-enzymatic and enzymatic resistance mechanisms thus remaining a challenge to even novel antibiotics including recently developed β-lactam and β-lactamase inhibitor combinations. This study shows that the novel β-lactam enhancer approach enables cefepime/zidebactam to overcome both non-enzymatic and enzymatic resistance mechanisms associated with a challenging panel of P. aeruginosa. This study highlights that the β-lactam enhancer mechanism is a promising alternative to the conventional β-lactam/β-lactamase inhibitor approach in combating ever-evolving MDR P. aeruginosa.